SPEECH ACT ANALYSIS ON INSTAGRAM CAPTION USED BY STUDENTS OF MUHAMMADIYAH UNIERSITY OF PONOROGO - Santi Patimah; Siti Asiyah; Diyah Atiek Mustikawati (Universitas Muhammadiyah Ponorogo, 2018)
Speech act is an act that a speaker or writer performs when making an utterance that could be found in Instagram caption made by students of Muhammadiyah University of Ponorogo. The purpose of this study was to identify the types of speech act, to describe the context based on the illocutionary act and to describe the maxim contained in the instagram caption. The subjects in this study were students of English education at the Muhammadiyah University of Ponorogo in the academic year 2017/2018. The data source obtained from caption Instagram written by English education student at Muhammadiyah University of Ponorogo. While the method used in this research is non-participant observation. From 41 data captions found based on the results of the study showed three types of speech act that were 21 showed assertive act because this speech act was used to overcome certain ideas or beliefs, for example confirming, informing, concluding or predicting something. And 7 data showed the directive act which was said to get permission to do something, such as asking and suggesting. From13 data showed expressive act was to express the speaker's feelings, such as feelings of gratitude, happiness, sadness, miss, sense of spirit or motivation etc. Meanwhile, from the results of the study also found 41 data of maxims that were 11 maxim of quantity, where the statement or utterance that was spoken effective, efficient and not many repetition. From 16 data maxim of quality that delivered that was truth with evidence and the 14 data of maxim relevancy which was conveyed there was a clear relationship between meaning and context, and then 3 data maxim of manner was maxim that was not exaggerated and not ambiguous.